Experimental model of Achilles tendon injury in rats - Akamatsu,Flavia Emi (2014)
PURPOSE:To describe an effective experimental model to study the Achilles tendon healing.METHODS:Forty male Rattus norvegicus albinus,Wistar lineage adult male weighing 250 to 300g were used for this experiment and thirty were surgically submitted to bilateral partial transverse section of the Achilles tendon. The right tendon was treated with radio waves (RF) whereas the left tendon served as control. On the third postoperative day, the rats were divided into four experimental groups consisting of ten rats each which were treated with monopolar RF adjusted to 650 kHz and 2w, for two minutes twice a week and a group of normal animals without any intervention, until they were sacrificed on the 7th, 14th and 28th days, respectively. Tendons were weighed and collagen quantification was evaluated by hydroxyprolin content.RESULTS:Significant reduction in collagen content on day 7, 14 and 28 was related to control experiment to normal tendon (7 days, p<0.01; 14 e 28 days, p<0.05).CONCLUSION:The experimental model has been effective and available to be used to study Achilles tendon healing.